Inglourious Basterds - Richardson, Robert 1955-; Biedrzycka-Sheppard, Anna; Pitt, Brad 1963-; Waltz, Christoph 1956-; Laurent, Mélanie 1983-; Brühl, Daniel 1978-; Schweiger, Til 1963-; Wuttke, Martin 1962-; Diehl, August 1976-; Fassbender, Michael 1977-; Kruger, Diane 1976-; Roth, Eli 1972- (Universal Pictures, 2009)
During World War II, a group of Jewish-American guerilla soldiers, led by Lt. Aldo Raine, become known as "The Basterds." They are chosen specifically to spread fear throughout the Third Reich by scalping and brutally killing Nazis. The Basterds soon cross paths with a French-Jewish woman who runs a movie theater in Paris which is targeted by the soldiers. A plot is set in motion to kill the Nazis at the theater's movie premier, including Adolph Hitler.
Aspect ratio 2.40:1 (anamorph widescreen)
Orig.: USA, Deutschland 2009
Enth. erweiterte und alternative Szenen ; "Stolz der Nation" - kompletter Film
Keywords: Hitler, Adolf <1889-1945> -- Assassination attempts -- Drama; Guerra Mundial II, 1939-1945 - Participación judío - Teatro; Judíos - Francia - Teatro; Frau; Juden; Weltkrieg (1939-1945); Jews -- France -- Drama; World War, 1939-1945 -- Motion pictures and the war -- Drama; World War, 1939-1945 -- Participation, Jewish -- Drama; World War, 1939-1945 -- Propaganda -- Drama; World War, 1939-1945 -- Women -- France -- Drama; World War, 1939-1945 -- France -- Drama; Frankreich; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired; War films